Magnetic levitation lighting kit / Atifah Nor Zulaikha Moktar, Muhammad Akram Radzuan and Nurul Aqilah Che Mood - Moktar, Atifah Nor Zulaikha; Radzuan, Muhammad Akram; Che Mood, Nurul Aqilah (2018)
In this modern era, busyness is more than just a companion. Thus, our team foresee the responsibility in designing a device that really care for those who always work on the go to really work at their utmost efficiency and comfort ability. Unlike any others, this product (magnetic levitation lighting kit) combine the technology of eye scanning and magnetic levitation to not just upgrading the culture of portable workspace but also maintaining good eye vision.